2014
DOI: 10.1371/journal.pone.0104345
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Modulates Mitochondria Dynamics in Replicative Senescent Yeast Cells

Abstract: Mitochondria form a reticulum network dynamically fuse and divide in the cell. The balance between mitochondria fusion and fission is correlated to the shape, activity and integrity of these pivotal organelles. Resveratrol is a polyphenol antioxidant that can extend life span in yeast and worm. This study examined mitochondria dynamics in replicative senescent yeast cells as well as the effects of resveratrol on mitochondria fusion and fission. Collecting cells by biotin-streptavidin sorting method revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…52,53 One prior study found resveratrol altered expression of mitochondrial fusion and fission genes in replicative senescent yeast cells. 54 Therefore, we have provided observational support for resveratrol's protective effects within the retina by activating OPA1.We found OPA1 protein expression increased following NMDAinduced retinal damage in the zebrafish retina, as reported previously. 55 Some studies also showed that glutamate receptor activation triggered OPA1 release and had the potential for proteolytic processing of OPA1.…”
Section: Discussionsupporting
confidence: 86%
“…52,53 One prior study found resveratrol altered expression of mitochondrial fusion and fission genes in replicative senescent yeast cells. 54 Therefore, we have provided observational support for resveratrol's protective effects within the retina by activating OPA1.We found OPA1 protein expression increased following NMDAinduced retinal damage in the zebrafish retina, as reported previously. 55 Some studies also showed that glutamate receptor activation triggered OPA1 release and had the potential for proteolytic processing of OPA1.…”
Section: Discussionsupporting
confidence: 86%
“…Drp1 lacks a mitochondrial destination sequence, and multiple receptors are capable of recruiting Drp1 to mitochondria to induce fission [ 63 ]. In yeast (for example, Saccharomyces cerevisiae ), Fzo1(fuzzyonions), a large GTPase belonging to the mitofusin family of proteins, joined with Mgm1 (mitochondrial genome maintenance), an ortholog of OPA1, are the main profusion proteins, while Dnm1 (dynamin-related), also a large GTPase, is recruited in the fission complexes with Fis1, Mdv1, and Caf4 at the mitochondrial outer membrane [ 106 ]. It has been argued that this kind of organellar dynamics is required to efficiently distribute mitochondria throughout the cell and generate highly interconnected networks that can facilitate efficient diffusive search processes [ 107 ] and play a key role in maintaining the integrity of the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the cells treated with ethanol activated the antioxidant machinery earlier, to counteract the effects of oxidative stress at the beginning of growth, thereby exhibiting higher oxidative stress tolerance [ 78 ]. The induction of these enzymes by ethanol has been widely reported [ 12 , 22 , 49 , 74 , 79 ], highlighting the importance of both SODs and the cytosolic catalase for ethanol tolerance [ 13 , 15 , 21 , 23 , 48 , 53 ]. In this study, catalase was clearly activated during the stationary phase, but SOD also presented high activity during the exponential phase, with a profile similar to that of lipid peroxidation, suggesting that SOD is activated before catalase.…”
Section: Discussionmentioning
confidence: 99%